The Comparison Of Problem-Based Learning And Explicit Instruction Model For Maintaining Environmental Sustainability In Primary Schools Of Manado City - Treesje K Londa; Olivia J Lalamentik (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2021)
Improving learning at the elementary school level can be done by implementing innovative learning models. Explicit problem based models that can be used by teachers in teaching and for students through active and enjoyable learning processes. The teacher's ability is measured using two Teacher Performance Assessment Instruments while student success is measured by achieving learning outcomes. This study compares problem-based learning and the application of explicit learning learning models with the theme of preserving the environment in Manado's elementary schools aimed at improving student learning outcomes for science subjects for elementary schools by comparing problem-based learning and explicit teaching models and creating a learning environment in learning environment for elementary school students class I to VI by comparing the use of problem-based learning and explicit teaching models. The results of the study show that environmental studies in elementary schools can be implemented using a learning model that fits the abilities of elementary school students at each level. Problem-based learning models can improve student learning outcomes. The explicit learning learning model can improve student learning outcomes. Problem-based learning and explicit teaching models can create a pleasant atmosphere for student learning. Problem-based learning and explicit teaching models can shape and develop better character of students in school to preserve and love the environment.